Correlation between Hemostasis Profile and Sepsis Outcome - Sisi Melansi; Eny Rahmawati; Susilawati Susilawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Sepsis is an organ dysfunction caused by infection. Excessive cytokine activation, which causes hemostasis disorder israted by Prothrombin Time (PT), activated Partial Thromboplastin Time (aPTT), fibrinogen, and D-dimer tests. Hemostasisdisorder can affect several sepsis outcomes (mortality and duration of treatment period). This study aimed to determine thecorrelation between hemostasis profile and sepsis outcome. This research was an analytical-observational withretrospective cohort study design with subjects consisting of 76 sepsis patients at Dr. Mohammad Hoesin Hospital,Palembang. The data were obtained by medical record observation and analyzed by Chi-Square and Spearman tests. From76 sepsis patients, 76.7% of subjects had normal PT; 88.2% had normal aPTT; 71.1% had elevated fibrinogen, and 100% hadelevated D-dimer. The patients' sepsis outcomes showed that 67.1% survived, and 32.9% has died, and the duration of thetreatment period without much differences is as long as ≤ 12 days and > 12 days. The statistical analysis showed that therewas no significant relationship between PT, mortality, duration of the treatment period (p=1.000; p=0.418), between aPTT,mortality, duration of the treatment period (p=0.709; p=0.480), between fibrinogen, mortality, duration of the treatmentperiod (p=0.350; p=1.000), and there was a weak negative correlation between D-dimer mortality and duration of thetreatment period (p=0.459; p=0.939). It could be concluded that there was no significant correlation between hemostasisprofile and sepsis outcome.